Developing an Australian Melanoma Clinical Outcomes Registry (MelCOR): a protocol paper. Issue 9 (2nd September 2022) - Jobson, Dale; Roffey, Benjamin; Best, Renee; Button-Sloan, Alison; Cossio, Danica; Evans, Sue; Shang, Catherine; Moore, Julie; Arnold, Christopher; Mann, Graham; Shackleton, Mark; Soyer, H Peter; et al.
Abstract : Introduction: Australia has the highest incidence of melanoma in the world with variable care provided by a diverse range of clinicians. Clinical quality registries aim to identify these variations in care and provide anonymised, benchmarked feedback to clinicians and institutions to improve patient outcomes. The Australian Melanoma Clinical Outcomes Registry (MelCOR) aims to collect population-wide, clinical-level data for the early management of cutaneous melanoma and provide anonymised feedback to healthcare providers. Methods and analysis: A modified Delphi process will be undertaken to identify key clinical quality indicators for inclusion in the MelCOR pilot. MelCOR will prospectively collect data relevant to these quality indicators, initially for all people over the age of 18 years living in Victoria and Queensland with a melanoma diagnosis confirmed by histopathology, via a two-stage recruitment and consent process. In stage 1, existing State-based cancer registries contact the treating clinician and provide an opportunity for them to opt themselves or their patients out of direct contact with MelCOR. After stage 1, re-identifiable clinical data are provided to the MelCOR under a waiver of consent. In stage 2, the State-based cancer registry will approach the patient directly and invite them to opt in to MelCOR and share identifiable data. If a patient elects to opt in, MelCOR will be able to contact patients directly to collect patient-reported outcome measures. Aggregated data will be used to provide benchmarked, comparative feedback to participating institutions/clinicians. Ethics and dissemination: Following the successful collection of pilot data, the feasibility of an Australia-wide roll out will be evaluated. Key quality indicator data will be the core of the MelCOR dataset, with additional data points added later. Annual reports will be issued, first to the relevant stakeholders followed by the public. MelCOR is approved by the Alfred Ethics Committee (58280/127/20).